2012
DOI: 10.4103/0975-3583.95365
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of hypertension and hypertension risk factors in a rural Indian community: A prospective door-to-door study

Abstract: Background:The aim of this study was to identify the prevalence and risk factors for hypertension in a rural community in north-east India.Materials and Methods:A door-to-door survey was conducted amongst all residents of a village in Uttarakhand province. All residents were interviewed and data were was relating to the demographics of the individuals, dietary habits, alcohol consumption, tobacco use, psychosocial stress, past medical history and drug history. Blood pressure (BP) and anthropometric data was re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
60
3
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(76 citation statements)
references
References 20 publications
11
60
3
2
Order By: Relevance
“…It has been demonstrated that among women high BP was significantly dependent on the age (U = 10,513.5; z = -5.117), BMI (U = 9,635; z = -5.832), WHR (U = 12,738; z = -2.888) and level of cholesterol (U = 2,827.5; z = -2268). Among men, the significant factors involved in the development of hypertension were age, BMI, and stress level [17].…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that among women high BP was significantly dependent on the age (U = 10,513.5; z = -5.117), BMI (U = 9,635; z = -5.832), WHR (U = 12,738; z = -2.888) and level of cholesterol (U = 2,827.5; z = -2268). Among men, the significant factors involved in the development of hypertension were age, BMI, and stress level [17].…”
Section: Discussionmentioning
confidence: 99%
“…Hypertension was characterized as BP ≥140 mmHg systolic and ≥90 mmHg diastolic BP. This is as per the joint national committee V criteria [4]. Participants having systolic and diastolic blood pressure less than the standard reading is considered to be normotensive, and participants with higher reading are considered to be hypertensive.…”
Section: Measurementsmentioning
confidence: 99%
“…Furthermore, India is undergoing a rapid economic growth. This growth has been accompanied by lifestyle changes which have had a large impact on the health profile of India's citizens and placed a significant strain on the country's healthcare system (6,7) . Hence, a survey covering the major cities of all Indian states was undertaken to assess the Hypertension, associated factors and its management in the day to day clinical scenario in India.…”
Section: Introductionmentioning
confidence: 99%